2022
DOI: 10.1021/acsenergylett.2c01955
|View full text |Cite
|
Sign up to set email alerts
|

Polyquinone Modification Promotes CO2 Activation and Conversion to C2+ Products over Copper Electrode

Abstract: Electrocatalytic CO 2 reduction to value-added chemicals is a promising route to address the global warming problem. However, it still confronts low conversion efficiency and poor selectivity, due to difficulties in activating the inert CO 2 molecule and controlling the complex reaction pathways. Here, we put forward an unconventional approach to activating CO 2 by utilizing the quasi-reversible bonding between electrochemically reduced quinone groups and CO 2 . Through surface modification with polyquinone, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…Stabilizing reaction intermediates is important to improve the conversion efficiency and yield of target products. It is an effective way to solve this problem to combine catalytic materials with polymers 76,[94][95][96][97][98] . It has been found that when polymers are combined with inorganic catalysts, the polymer-specific groups can regulate the electronic structure of the catalysts and the state of their surface microenvironment during the reaction.…”
Section: Stabilization Of Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stabilizing reaction intermediates is important to improve the conversion efficiency and yield of target products. It is an effective way to solve this problem to combine catalytic materials with polymers 76,[94][95][96][97][98] . It has been found that when polymers are combined with inorganic catalysts, the polymer-specific groups can regulate the electronic structure of the catalysts and the state of their surface microenvironment during the reaction.…”
Section: Stabilization Of Intermediatesmentioning
confidence: 99%
“…Li et al activated CO2 by using the quasi-reversible bond between electrochemical reduction quinone group and CO2 96 . By further incorporating hydroquinone into the Cu GDEs, a high C2H4 partial current density of 325 mAꞏcm −2 is achieved at a low battery voltage of 3 V for CO2/pure water co-electrolysis.…”
Section: Stabilization Of Intermediatesmentioning
confidence: 99%
“…By impregnating QAPEEK ionomer into the porous Cu GDE to further increase the ESA (Figure 17e), the CO 2 /pure water co‐electrolyser reached a C 2 H 4 partial current density of 420 mA cm −2 at a cell voltage of 3.54 V (Figure 17f). Recently, the same group has found that polyquinone can accelerate CO 2 ‐to‐*CO conversion, creating a high *CO coverage on Cu surface and thus facilitating C−C coupling for C 2+ generation [121] …”
Section: Application Of Membrane Electrode Assemblies For Co2 Reductionmentioning
confidence: 99%
“…Recently, the same group Angewandte Chemie Aufsätze has found that polyquinone can accelerate CO 2 -to-*CO conversion, creating a high *CO coverage on Cu surface and thus facilitating CÀ C coupling for C 2 + generation. [121] Apart from the above methods based on catalyst design for C 2 + production towards CO 2 RR, cascade CO 2 electroreduction via a two-step process is another alternative for C 2 + generation. Here CO 2 will be first reduced to CO and then CÀ C coupling will be achieved in the second step of CO to C 2 + .…”
Section: Formation Of C 2 + Productsmentioning
confidence: 99%
“…80 The organic polymers with tunable functional groups can effectively stabilize intermediates and are ideal for improving the catalytic activity of Cu catalysts. 81 Amino group is a kind of Lewis base which affinity for CO 2 and intermediates that has been demonstrated to be work in C-C coupling. Polyaniline (PANI) is a star conductive polymer that has been widely studied in energy storage and conversion, including CO 2 RR.…”
Section: Coverage Of Intermediatesmentioning
confidence: 99%